2001
DOI: 10.1093/aje/153.12.1183
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Serum C-Reactive Protein and Its Association with Atherosclerotic Risk Factors in a Japanese Population : Jichi Medical School Cohort Study

Abstract: The distribution of serum C-reactive protein (CRP) levels and their association with age, sex, and atherosclerotic risk factors were studied in a large Japanese population between 1992 and 1995. The subjects consisted of 2,275 males and 3,832 females aged 30 years and over. CRP was measured by nephelometry. The distribution of CRP was highly skewed toward a lower level than that of previous studies and seemed to be a combination of two separate distribution curves. The increase in CRP with age was statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
166
6
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(207 citation statements)
references
References 32 publications
29
166
6
6
Order By: Relevance
“…Also, it is well known that menopause aggravates the progression of atherosclerosis, 28 and the CRP level of female subjects is lower than that of male subjects. 29 The baPWV of female subjects was significantly lower than that of male subjects in subjects p55 years old, 27 so CRP in younger female subjects might have a limited effect on arterial stiffness.…”
Section: Discussionmentioning
confidence: 94%
“…Also, it is well known that menopause aggravates the progression of atherosclerosis, 28 and the CRP level of female subjects is lower than that of male subjects. 29 The baPWV of female subjects was significantly lower than that of male subjects in subjects p55 years old, 27 so CRP in younger female subjects might have a limited effect on arterial stiffness.…”
Section: Discussionmentioning
confidence: 94%
“…Gender differences in CRP concentrations is currently a controversial topic. Some epidemiological studies have reported similar values for CRP in both men and women (7,8), whereas others have shown higher concentrations in men (9) or women only (10,11).…”
Section: Introductionmentioning
confidence: 94%
“…It has been suggested that the insulin resistance syndrome may be associated with increased serum CRP levels and visceral obesity [5][6][7]. Correlations between serum CRP and body mass index (BMI) and waist circumference have also been shown [6][7][8]. Although waist circumference has been used as a crude measure of visceral obesity, direct measurement of the visceral and subcutaneous adipose tissue areas by computed tomography (CT) is currently considered to be a more precise method.…”
mentioning
confidence: 99%